Identification of regional French accents in (northern) France, Belgium, and Switzerland. Issue 1 (10th August 2017) - Avanzi, Mathieu; de Mareüil, Philippe Boula
Abstract : This paper investigates whether European Francophone subjects are able to distinguish between regional French accents from (northern) France, Belgium, and Switzerland, and at what level of granularity. In total, samples from 120 speakers (from five different areas in each country under study) were presented to hundreds of native French listeners from these three countries. In a first set of experiments, listeners were asked to identify the speakers' country of origin: they achieved 60% correct identification on average, with significant effects of listeners' region of origin, speakers' age, socioeconomic status, and region of origin. In a second set of experiments, listeners from Belgium, France, and Switzerland were asked to identify the speakers' region of origin within each country (5-alternative forced choice). Results, albeit above chance, proved to be poorer than they were in the first set of experiments (31% correct identification on average). Complementary analyses were conducted to evaluate the role of listeners' region of origin, speakers' age, speakers' region of origin, and their interaction. They showed asymmetrical response patterns across the three countries under investigation: France (or, within France, Paris, which represents the norm) seems to act as a magnet and a catalyst of unification. Younger generations, especially, are more often associated with its way of speaking when their accent is not clearly identifiable. Switzerland, though, resists this homogenizing process better than Belgium does.